Properties of the category of neutrosophic subgroups - Saeid Jafari; Neelamegarajan Rajesh; Giorgio Nordo; Carmelo Cisto (Neutrosophic Sets and Systems)
In this paper, we introduce the notions of inverse and direct systems in the category of neutrosophic M-groups and examine their fundamental properties. In particular, we explore the behavior of limits in such systems, focusing on whether inverse and direct limits preserve exactness in sequences of neutrosophic Mgroups.